Equity and access to health care services: the experience of the Bamako initiative programme in Nigeria (2012)
This study examines attempts by the Nigerian government to increase the access of the poorest people to modern health care services, through the Bamako Initiative programme. Responses obtained from health service providers and consumers, as well as community leaders selected from across the four health zones in Nigeria, showed a conclusion that although the operational structures to accomplish the Bamako initiative objectives are in place, access to health services by the poorest is still difficult. The operation of the programme in this direction also runs parallel to existing Nigerian traditional structures to accommodate the indigent in the community. The study suggests that both structures need to be integrated to increase access to health care services